Redefining Teaching Planning: Innovations and curriculum adjustments intimes of change (Research, Society and Development, 2024)
The general objective of this research is to analyze the updating of teaching planning taking into account the changes made in the curricular adaptation in an educational center in the Dominican Republic. This study is focused on the positivist paradigm with a field-level descriptive quantitative approach. To carry out the investigation, the total population of active teachers at the center was selected, in this case 12 teachers belonging to the different curricular areas. The technique used to collect information is the survey, the instrument was the questionnaire, which is made up of 15 items with answers of several alternatives. To analyze the data and obtain the relative and absolute frequency and generate the graphs, descriptive statistics are used, using SPSS and Microsoft Excel. It concluded that there is an identification in the transformations carried out to update teaching planning and the changes made to the Dominican curriculum. Additionally, the contribution to the improvement of pedagogical practice and student performance, aligning pedagogical actions with the interests and needs of teachers in the school institution.